Constituting Human Rights: Global Civil Society and The Society of Democratic States - Mervyn Frost (Routledge, 2002)
Global civil society and the society of democratic states are the two most inclusive and powerful global practices of our time. In this book, Frost claims that, without an understanding of the role that individual human rights play in these practices, no adequate understanding of any major feature of contemporary world politics from 'globalisation' to 'new wars' is possible. Constituting Human Rights, therefore argues that a concern with human rights is essential to the study of International Relations